2017
DOI: 10.1177/1076029617716769
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the CHA2DS2-VASc Score in Predicting In-Stent Restenosis Among Patients Undergoing Revascularization With Bare-Metal Stents

Abstract: In-stent restenosis (ISR) is a limitation of percutaneous coronary intervention and has been linked to specific clinical and angiographic variables. The aim of the present study was to investigate the predictive value of preprocedural CHA2DS2-VASc score on ISR in patients undergoing revascularization with bare-metal stent (BMS) implantation for stable coronary artery disease or acute coronary syndrome. In the years 2012 to 2014, a total of 358 consecutive patients (mean age: 62.36 + 11.28 years and 62.2% men) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Therefore, the score was matched against the outcomes of several diseases such as atrial fibrillation with pulmonary embolism, chronic obstructive pulmonary disease with or without AF, decreased left ventricular ejection fraction, and coronary artery disease. 12,21-25 In this study, we firstly investigated the association of the CHA2DS2-VASc score with the RVD, clinical subgroups, and in-hospital mortality. In addition to the abovementioned studies, in this study, we found that the CHA2DS2-VASc score was significantly different among the clinical subgroups in patients with acute PTE and determined that the CHA2DS2-VASc score was an independent predictor of the RVD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the score was matched against the outcomes of several diseases such as atrial fibrillation with pulmonary embolism, chronic obstructive pulmonary disease with or without AF, decreased left ventricular ejection fraction, and coronary artery disease. 12,21-25 In this study, we firstly investigated the association of the CHA2DS2-VASc score with the RVD, clinical subgroups, and in-hospital mortality. In addition to the abovementioned studies, in this study, we found that the CHA2DS2-VASc score was significantly different among the clinical subgroups in patients with acute PTE and determined that the CHA2DS2-VASc score was an independent predictor of the RVD in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies reported elevations in the CHA 2 DS 2 -VASc scores in patients in the ISR groups compared with the non-ISR groups. 11,12 Their multivariate logistic regression analyses showed that the CHA 2 DS 2 -VASc score was an independent risk factor for ISR in patients after BMS implantation, and they concluded that the CHA 2 DS 2 -VASc score was a simple effective means of predicting ISR in those patients. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…This current study demonstrated that the CHA 2 DS 2 -VASc score and the CHA2DS2-Vasc-HS score were not associated with an increased risk of ISR in individuals undergoing revascularization with DES, which is in contrast with the findings of two earlier BMS studies. 11,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of these two scores are associated with atherosclerosis, vascular spasm, and microvascular dysfunction, which overlap the risk factors of NRP [7]. Several recent studies have also shown that the CHA 2 DS 2 -VASc scores are associated with the severity of coronary artery disease, its prognosis, and NRP in patients with acute MI, contrast-induced nephropathy after PPCI for acute coronary syndrome, in-stent restenosis, acute stent thrombosis, mechanical mitral valve thrombosis, and right ventricular dysfunction [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%